Challenges and recommendations to improve implementation of phototherapy among neonates in Malawian hospitals - Mai-Lei Woo Kinshella; Sangwani Salimu; Brandina Chiwaya; Felix Chikoti; Lusungu Chirambo; Ephrida Mwaungulu; Mwai Banda; Tamanda Hiwa; Marianne Vidler; Elizabeth M. Molyneux; Queen Dube; Joseph Mfutso-Bengo; et al. (BMC, 2022)
Abstract Background Severe neonatal jaundice can result in long term morbidities and mortality when left untreated. Phototherapy is the main-stay intervention for treating moderate jaundice and for prevention of the development of severe jaundice. However, in resource-limited health care settings, phototherapy has been inconsistently used. The objective of this study is to evaluate barriers and facilitators for phototherapy to treat neonatal jaundice at Malawian hospitals. Methods We conducted a convergent mixed-method study comprised of a facility assessment and qualitative interviews with healthcare workers and caregivers in southern Malawi. The facility assessment was conducted at three secondary-level hospitals in rural districts. In-depth interviews following a semi-structured topic guide were conducted at a district hospital and a tertiary-level hospital. Interviews were thematically analysed in NVivo 12 software (QSR International, Melbourne, Australia). Results The facility assessment found critical gaps in initiating and monitoring phototherapy in all facilities. Based on a total of 31 interviews, participants identified key challenges in diagnosing neonatal jaundice, counselling caregivers, and availability of infrastructure. Participants emphasized the need for transcutaneous bilirubinometers to guide treatment decisions. Caregivers were sometimes fearful of potential harmful effects of phototherapy, which required adequate explanation to mothers and family members in non-medical language. Task shifting and engaging peer support for caregivers with concerns about phototherapy was recommended. Conclusion Implementation of a therapeutic intervention is limited if accurate diagnostic tests are unavailable. The scale up of therapeutic interventions, such as phototherapy for neonatal jaundice, requires careful holistic attention to infrastructural needs, supportive services such as laboratory integration as well as trained human resources.